KONDISI MASYARAKAT MISKIN DI KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA (Studi Kasus Desa Sungai Kakap Kec. Sungai Kakap Kab. Kubu Raya) - B01109056, Ridwansyah (Jurnal Pembangunan dan Pemerataan, 2013)
The study is titled "The condition of the Poor in District Sungai Kakap District Kubu Raya (Case Study of the Village Sungai Kakap District Sungai Kakap District Kubu Raya)" aims to determine the socio- economic characteristics of the condition of the poor in the District Sungai Kakap District Kubu Raya and to determine the government's efforts to poverty alleviation in District Sungai Kakap District Kubu Raya. The method used in this study is the method by using the technique of primary and secondary data collection, through interviews (interviews) respondents and resource persons from government agencies and community leaders by distributing questionnaires that have been compiled before, and sources of data obtained directly of the agencies that provide the necessary data. As well as by way of sampling methods on the object that will be investigated are selected using purposive sampling (samples intended). Discussion of the results showed that the condition of the poor in the village of Sungai Kakap District Sungai Kakap District Kubu Raya residing the area have an average job, and the majority of poor people are in the age of reproductive age, but the income received from such work are not fixed and relatively small, so that in fulfilling the needs of daily life is still meager. In addition, the level of Human Resources (HR) inadequate as: low level of education , low skill levels and low levels of health, so that poor people trapped in poverty. Various government efforts in poverty alleviation programs and the government had taken the program felt that the government is still not optimal and in particular in the area of ??temporary District Sungai Kakap District Kubu Raya. Keywords : People, Poverty, Income